Development of PBL-STEM-based E-LKPD to improve students' science literacy skills on reaction rate materials - Rina Safitri; Haryanto Haryanto; Harizon Harizon (Pascasarjana Universitas Negeri Medan, 2021)
The development model used is Research & Development which adopts the Lee & Owens development model. The product to be developed is E-LKPD using 3D Pageflip Professional software. 1. The procedure for developing E-LKPD with the PBL-STEM approach in improving scientific literacy skills on the reaction rate material for students. The research procedure consists of five stages, namely analysis, design, development, implementation, evaluation. Research results (1) The analysis includes media analysis, student characteristics analysis, technology analysis, situation analysis, and data analysis. (2) Design includes determining the development team, compiling a development schedule, making flowcharts and making storyboards. (3) Development includes making a product which is then validated by a team of experts until it is validated. (4) Implementation, at this stage a product assessment is carried out by 2 chemistry teachers to see the agreement between the two teachers on the product developed through the kappa test, one-on-one trial with 2 groups of respondents consisting of 3 students in each group, small group trial with two groups of respondents carried out at MAN 2 Jambi City. This trial is not conducted face-to-face, but online (5) Evaluation, which is carried out at each stage is ongoing. The conclusion in this study is that the E-LKPD development procedure is in accordance with the 5 stages of the Lee & Owens development model. Keywords: E-LKPD, PBL-STEM, Science literacy skills